1978
DOI: 10.3109/00498257809060953
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Papaverine: IV. Urinary Elimination of Papaverine Metabolites in Man

Abstract: 1. A gas chromatographic method is described for the quantitative determination of the metabolites of papaverine in urine. 2. The urinary excretion of papaverine metabolites was studied in man. About 50% of the metabolites of papaverine are excreted in the urine within 48 h. 6-Desmethylpapaverine is the major metabolite in the urine. The metabolites are excreted almost completely in conjugated form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…20 Two other poppy alkaloids, noscapine and papaverine, are extensively metabolized in humans, with less than 1% of the unchanged drug excreted in the urine. 22,23 Despite the ability of the UDAS method to detect these alkaloids (Table 1), neither were detected in urine of the study population; however, there was evidence for the presence of metabolites of both of these compounds. Meconine and desmethylmeconine are urinary metabolites of noscapine, and have been reported to account for approximately 2± 3% and 7± 75%, respectively, of an oral dose of the drug.…”
Section: Discussionmentioning
confidence: 92%
“…20 Two other poppy alkaloids, noscapine and papaverine, are extensively metabolized in humans, with less than 1% of the unchanged drug excreted in the urine. 22,23 Despite the ability of the UDAS method to detect these alkaloids (Table 1), neither were detected in urine of the study population; however, there was evidence for the presence of metabolites of both of these compounds. Meconine and desmethylmeconine are urinary metabolites of noscapine, and have been reported to account for approximately 2± 3% and 7± 75%, respectively, of an oral dose of the drug.…”
Section: Discussionmentioning
confidence: 92%
“…These observations are consistent with rapid in vivo clearance of [ 11 C]papaverine from PDE-10 enriched areas of the CNS in rats. Our imaging data may indicate that the 30 nM binding affinity of papaverine, when coupled with a reduced input function due to rapid clearance of papaverine from the blood result in CNS binding kinetics which are unsuitable for a radiotracer [10, 17]. Although clinical PET imaging studies with Carbon-11 tracers seldom require prolonged retention in target-areas, the radioactivity uptake ratios of [ 11 C]papaverine in both caudate and putamen to cerebellum at the time of transient equilibrium (10 min post injection) was close to unity, as can be inferred from the data shown in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a comparison with previously published studies concerning alkaloid concentrations of poppy seed products revealed fluctuating morphine concentrations within the same product. Due to an extensive metabolism of noscapine and papaverine in human body, coupled with a short half-life of papaverine (0.8-1.5 h), [17][18][19] urinary detection after poppy seed ingestion is rather unlikely. In contrast, in this study a morphine concentration of merely 0.649 μg/g could be confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…[12,15,16] Similar to the results published by Trafkowski et al, [16] neither noscapine nor papaverine were detectable in urine samples after consumption of poppy seeds containing up to 37 μg noscapine and up to 9.8 μg papaverine. Due to an extensive metabolism of noscapine and papaverine in human body, coupled with a short half-life of papaverine (0.8-1.5 h), [17][18][19] urinary detection after poppy seed ingestion is rather unlikely. Though, proof of these natural occurring poppy seed alkaloids in urine following consumption of poppy seed products with particularly high levels of these alkaloids cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%